Nation-building a key concept for peaceful conflict transformation? - Hippler, Jochen (Pluto in association with the Development and Peace Foundation, Bonn, 2005)
The term 'nation-building' has experienced a remarkable renaissance since the early 1990s. It has been used to describe and to justify the military interventions in Somalia, Afghanistan and Iraq. Linked to the idea of 'failed' or 'failing' states, the concept is used to hide and legitimise a whole range of diverse policies, allowing foreign powers to control and reshape countries in areas of conflict.